Kebutuhan Belajar Orang Dewasa dalam Meningkatkan Ilmu Keagamaan pada Kegiatan Pengajian Ahad Pagi - Mutiara Lavida Ilma Nafiah; Sopingi Sopingi; Kukuh M Raharjo; Mutiara Lavida Ilma Nafiah; Sopingi Sopingi (Universitas Negeri Malang, 2023)
Abstract: Lack of community involvement in social and religious activities in the environment around the mosque is one of the problems that needs attention to create a human resource that has faith as the foundation of one's life, especially in Islamic spiritual field. The decreasing level of community involvement in this mosque environment demands the holding of community-based education in order to meet the learning needs of the community as adults. One of the activities that play a role in meeting social and religious needs is Sunday morning recitation activities with informal learning and the learning process can occur anywhere, including in a non-formal educational institution such as a taklim assembly. The aims of this research are 1). Describe the needs of adults in improving religious knowledge through Sunday morning recitation activities, 2). Describe the process of implementing Sunday morning recitation at the Baiturrahman Mosque in facilitating the learning needs of adults. This study uses a qualitative research method with a case study research type. This research was conducted at the Baiturrahman Tepus Mosque. The informants in this study were the chairman of the takmir, the vice chairman of the takmir, and the Sunday morning recitation congregation. Data collection techniques were carried out by interviews, observation, and documentation. Data analysis techniques used are data reduction, data presentation, and efforts to draw conclusions. Meanwhile, in this study, data validity was tested using source triangulation and technical triangulation. The research results obtained from this study are that the Sunday Morning Recitation Activities at the Baiturrahman Mosque are one of the informal learning facilities or containers that focus on the needs of Islamic religious learning for adults. In Sunday morning recitation activities, humans as adults need religious knowledge because humans as adults have obligations and responsibilities to God, therefore humans are required to continue learning in fulfilling the necessities of life and their religion as religious beings in this world. As for the process of implementing Sunday morning recitation activities in facilitating the learning needs of adults, starting from planning, organizing, implementing, and evaluating. Planning is carried out by holding meetings and deliberations to discuss the planning of Sunday morning activities. Organizing by forming a committee for Sunday morning recitation activities. Sunday morning recitation activities are held on Sunday or Sunday every two weeks. Evaluate activities to measure the success and constraints of the program that has been implemented as an evaluation of improvements for further activities. Abstrak: Minimnya keterlibatan masyarakat dalam kegiatan-kegiatan sosial dan keagamaan di lingkungan sekitar masjid merupakan salah satu permasalahan yang perlu diperhatikan untuk menciptakan suatu sumber daya manusia yang mempunyai keyakinan sebagai pondasi hidup seseorang khususnya di bidang spiritual keagamaan Islam. Menurunnya tingkat keterlibatan masyarakat di lingkungan masjid ini, menuntut diselenggarakannya pendidikan berbasis masyarakat dalam rangka memenuhi kebutuhan belajar masyarakat sebagai orang dewasa. Salah satu kegiatan yang berperan dalam memenuhi kebutuhan sosial dan keagamaan yaitu kegiatan pengajian ahad pagi dengan pembelajaran informal dan proses pembelajarannya dapat terjadi dimana saja, termasuk didalam sebuah lembaga pendidikan nonformal seperti majelis taklim. Tujuan dalam penelitian ini adalah 1). Mendeskripsikan kebutuhan orang dewasa dalam meningkatkan ilmu keagamaan melalui kegiatan pengajian ahad pagi, 2). Mendeskripsikan proses pelaksanaan pengajian ahad pagi di Masjid Baiturrahman dalam memfasilitasi kebutuhan belajar orang dewasa. Penelitian ini menggunakan metode penelitian kualitatif dengan jenis penelitian studi kasus. Penelitian ini dilaksanakan di Masjid Baiturrahman Tepus. Informan dalam penelitian ini adalah ketua takmir, wakil ketua takmir, dan jamaah pengajian ahad pagi. Teknik pengumpulan data dilakukan dengan wawancara, observasi, dan dokumentasi. Teknik analisis data yang digunakan yaitu reduksi data, penyajian data, dan upaya penarikan kesimpulan. Sedangkan dalam penelitian ini, uji keabsahan data menggunakan triangulasi sumber dan triangulasi teknik. Hasil penelitian yang diperoleh dari penelitian ini adalah Kegiatan Pengajian Ahad Pagi di Masjid Baiturrahman merupakan salah satu sarana atau wadah pembelajaran informal yang berfokus pada kebutuhan belajar keagamaan Islam bagi orang dewasa. Dalam kegiatan pengajian ahad pagi, manusia sebagai orang dewasa membutuhkan ilmu keagamaan karena manusia sebagai orang dewasa memiliki kewajiban dan tanggung jawab kepada Tuhan, oleh karena itu manusia dituntut untuk terus belajar dalam memenuhi kebutuhan hidup dan agamanya sebagai makhluk hidup yang beragama di dunia ini. Adapun proses pelaksanaan kegiatan pengajian ahad pagi dalam memfasilitasi kebutuhan belajar orang dewasa yaitu mulai dari perencanaan, pengorganisasian, pelaksanaan, dan evaluasi. Perencanaan dilakukan dengan mengadakan kegiatan pertemuan dan musyawarah membahas perencanaan kegiatan ahad pagi. Pengorganisasian dengan membentuk pengurus kegiatan pengajian ahad pagi. Pelaksanaan kegiatan pengajian ahad pagi dilaksanakan pada hari Minggu atau Ahad setiap dua minggu sekali. Melakukan evaluasi kegiatan untuk mengukur keberhasilan dan kendala program yang telah dilaksanakan sebagai evaluasi perbaikan untuk kegiatan selanjutnya.